Implementasi media kartu domino biologi untuk peningkatan pemahaman siswa pada materi sistem ekskresi - Sansena, Mona Anju; Rizkiyah, Fitri; Nikmah, Ani; Wulandari, Endang; Meliana, Sari (Jurnal Kajian Pendidikan IPA, 2024)
This study aims to implement biology domino card media as an alternative learning media and examine its effect on improving student understanding of excretory system material. The research used pre-experiment method with one group pretest-posttest design. The research subjects were all students of class XI IPA SMA IT Bina Pekerti as many as 23 students, with saturated sampling technique. The instruments used include concept understanding tests and student response questionnaires. The results showed an increase in the average score from the pretest of 48.7 to the posttest of 81.5 with an average N-Gain value of 0.64 (medium category). The paired sample t-test showed a significant difference (p < 0.05) between the pretest and posttest. Students' responses to the use of media also showed a very positive category. Based on these results, the biology domino card media is effectively used to improve student understanding of excretory system material in class XI. Keywords: Biology dominoes card, student understanding, excretory system.